2017
DOI: 10.1080/15384101.2017.1281484
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii induces autophagy and apoptosis in human umbilical cord mesenchymal stem cells via downregulation of Mcl−1

Abstract: Autophagy and apoptosis are critical for controlling Toxoplasma gondii (T. gondii) infection. T. gondii infection during pregnancy can damage the fetus and cause birth defects; however, the molecular mechanisms of this process are poorly understood. This study aims to determine the activities of autophagy and apoptosis as well as their regulatory mechanisms during T. gondii infection by using human umbilical cord mesenchymal stem cells (hUC-MSCs) as a model of congenital diseases. LC3B, a hallmark protein of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Subsequently, we further evaluated T. gondii-induced HTR8/SVneo cell viability, and the results showed that T. gondii infection significantly reduced cell viability, with viabilities of 82.83± 4.78%, 70.37± 7.77%, and 48.50± 3.49% observed for cells infected with T. gondii for 4, 8, and 48 hr, respectively. These findings are consistent with those of our previous study showing that GFP-RH (MOI 5) T. gondii infection of human umbilical cord mesenchymal stem cells significantly reduced viability by 21 and 30% in cells infected with T. gondii for 24 and 48 hr, respectively [18].…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, we further evaluated T. gondii-induced HTR8/SVneo cell viability, and the results showed that T. gondii infection significantly reduced cell viability, with viabilities of 82.83± 4.78%, 70.37± 7.77%, and 48.50± 3.49% observed for cells infected with T. gondii for 4, 8, and 48 hr, respectively. These findings are consistent with those of our previous study showing that GFP-RH (MOI 5) T. gondii infection of human umbilical cord mesenchymal stem cells significantly reduced viability by 21 and 30% in cells infected with T. gondii for 24 and 48 hr, respectively [18].…”
Section: Discussionsupporting
confidence: 93%
“…tTreg-related anti/pro apoptosis genes (Bcl-2, Bcl-xL, Mcl-1, c-myc, BAX, BID, and BAD) play a key role in cell survival 26 – 29 . Of them, Mcl-1, c-myc, BAX, and BID expression were related to cell autophagy, which is essential for cell cycle and function 30 32 . Therefore, we qualified these genes expression by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…When STs are infected, the resulting syncytial damage increases parasitic infection in the villous arms, foetal structures that are in contact with maternal blood . T. gondii infection of human umbilical cord‐derived mesenchymal stem cells induces autophagic cell death (also known as type II programmed cell death) . These reports demonstrate how T. gondii can potentially destroy placental cells and successfully cross the placental barrier to infect the foetus.…”
Section: Vertical Transmission Of Toxoplasma Gondii Infection During mentioning
confidence: 87%